National minimum wage and employment of young workers in the UK - Fidrmuc, Jan; Tena, Juan de Dios (Munich, 2013)
"We analyze the impact of the UK national minimum wage (NMW) on the employment of young workers. The previous literature found little evidence of an adverse impact of the NMW on the UK labor market. We focus on the age-related increases in the NMW at 18 and 22 years of age. Using regression discontinuity design, we fail to find any effect of turning 22. However, we find a significant and negative employment effect for male workers at 21, which we believe to be an anticipation effect. We also find a negative effect for both genders upon turning 18. The age-related NMW increases may have an adverse effect on employment of young workers, with this effect possibly occurring already well in advance of reaching the threshold age."